Role of hydrophobicity in adhesion of wild yeast isolated from ultrafiltration membranes of an apple juice processing plant - Tarifa, Maria Clara (2013)
The role of cell surface hydrophobicity in the adhesion to stainless steel (SS) of 11 wild yeast strains isolated from the ultrafiltration membranes of an apple juice processing plant was investigated. The isolated yeasts belonged to four species: Candida krusei (5 isolates), Candida tropicalis (2 isolates), Kluyveromyces marxianus (3 isolates) and Rhodotorula mucilaginosa (1 isolate). Surface hydrophobicity was measured by the microbial adhesion to solvents method. Yeast cells and surfaces were incubated in apple juice and temporal measurements of the numbers of adherent cells were made. Ten isolates showed moderate to high hydrophobicity and 1 strain was hydrophilic. The hydrophobicity expressed by the yeast surfaces correlated positively with the rate of adhesion of each strain. These results indicated that cell surface hydrophobicity governs the initial attachment of the studied yeast strains to SS surfaces common to apple juice processing plants.